Range extension of endemic butterflies in Western Mindanao, Philippines - Abijay, Leizel Mae R. (Philippine Journal of Science, 2023)
A recent assessment on the butterflies of Mount Gutom, Zamboanga del Norte, Mindanao, Philippines, resulted in range extensions of Mindanao endemic nymphalid butterflies such as Zethera hestioides and Zethera musa.